2017
DOI: 10.1007/s00280-017-3292-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased ceramide production sensitizes breast cancer cell response to chemotherapy

Abstract: This study clearly demonstrated that the decreased ceramide production via up-regulating UGCG was involved in the resistance of breast cancer cells to chemotherapy. Stimulating ceramide or decreasing UGCG can potentially be useful for breast cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Indeed, the use of ceramides as coadjuvant therapy with different antineoplastics, is a novel treatment option due to its multifactorial participation in the structure and function of MAMs [ 84 ]. In line with this notion, ceramides are bioactive lipids that modulate processes such as proliferation and cell cycle, key events in the development of cancer [ 19 , 20 ]. Various reports have shown that cancer cells strictly modulate ceramide metabolism [ 19 , 20 , 85 ].…”
Section: Role Of Mams In Neoplastic Pathologymentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the use of ceramides as coadjuvant therapy with different antineoplastics, is a novel treatment option due to its multifactorial participation in the structure and function of MAMs [ 84 ]. In line with this notion, ceramides are bioactive lipids that modulate processes such as proliferation and cell cycle, key events in the development of cancer [ 19 , 20 ]. Various reports have shown that cancer cells strictly modulate ceramide metabolism [ 19 , 20 , 85 ].…”
Section: Role Of Mams In Neoplastic Pathologymentioning
confidence: 99%
“…In line with this notion, ceramides are bioactive lipids that modulate processes such as proliferation and cell cycle, key events in the development of cancer [ 19 , 20 ]. Various reports have shown that cancer cells strictly modulate ceramide metabolism [ 19 , 20 , 85 ]. For instance, sphingolipid metabolism has been reported to regulate cancer development, progression, metastasis and resistance to therapy, some mechanisms have been described to explain how ceramides could regulate these processes specifically in breast cancer [ 19 , 20 ].…”
Section: Role Of Mams In Neoplastic Pathologymentioning
confidence: 99%
See 3 more Smart Citations